Inhibition of cellular alpha DNA polymerase and herpes simplex virus-induced DNA polymerases by the triphosphate of BW759U. - St Clair, M H (1984)
The triphosphate form of the acyclovir analog BW759U (9-[[2-hydroxy-1-(hydroxymethyl)ethoxy]methyl]guanine) inhibited the DNA polymerases (EC 2.7.7.7) from several strains of herpes simplex virus type 1. Two acyclovir triphosphate-resistant DNA polymerases were as sensitive to BW759U-triphosphate as were the DNA polymerases induced by wild-type viruses (Ki = 0.05 to 0.1 microM). The Ki value for cellular alpha DNA polymerase was 35- to 50-fold greater than those for the DNA polymerases induced by the various herpes simplex virus strains investigated. Incubation of Vero cells infected by the KOS strain of herpes simplex virus type 1 with the acyclovir analog resulted in the formation of substantial quantities of (9-[[2-hydroxy-1-(hydroxymethyl)ethoxy]methyl]guanine) triphosphate.